Karakteristik Perusahaan dan Good Corporate Governance Sebagai Determinan Internet Financial Reporting di Indonesia - Endra Wahyu Ningdiyah; Wahidahwati Wahidahwati; Nur Fadjrih Asyik (Akuntansi : Jurnal Akuntansi Integratif, 2021)
Abstract This study aims to determine the effect of company characteristics and corporate governance on internet financial reporting in pharmaceutical companies in Indonesia for the 2015-2019 period. Variables The characteristics of the companies examined in this study are company size, profitability, liquidity, leverage and company registered age, while corporate governance is measured by the structure of public ownership and the size of the board of commissioners. The sampling method used was purposive sampling method. The number of companies sampled in this study were 8 pharmaceutical companies listed on the IDX in the 2015-2019 period. The data used are secondary data. The data analysis method used in this research is logistic regression. The results of this study indicate that liquidity and leverage have an effect on the timeliness of IFRs. However, company size, profitability, company registered age, public ownership structure and board size do not affect the timeliness of IFRs.